Integrating Digital Technologies in Teaching Pencil Drawing in Higher Pedagogical Education - Sa’diyev Soli Tolipovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines the application of the flipped classroom method in teaching pencil drawing within higher pedagogical education. The study explores how pre-class theoretical learning, combined with in-class practical exercises and collaborative projects, enhances students’ technical skills, creativity, and professional competencies. The research emphasizes student-centered learning, active participation, and the development of independent problem-solving abilities.